Relationship Between Corporate Social Responsibility Disclosure, Corporate Governance, And Tax Avoidance - Maria Natalia; Verani Carolina; Joni Joni (Faculty of Business and Economics Universitas Atma Jaya Yogyakarta, 2021)
This study aims to examine the effect of corporatesocial responsibility disclosure on tax avoidance with corporate governance as moderation variable. The disclosure of corporate social responsibility in this study is measured using performance indicators from Global Reporting Initiative (GRI) 4.1. The score of corporate governance is measured using ASEAN CG Scorecard, while tax avoidance is measured by Cash ETR. The sample in this study is a manufacturing company listed on the Indonesia Stock Exchange in 2018. This study refers to Lanis and Richardson (2012) which found that, the higher the disclosure of social responsibility, the lower the tax avoidance. This study also refers to Salhi et al. (2019) which found that, if corporate governance has been performed well, companies are less likely to do tax avoidance. The results of the study showed that corporate social responsibility and corporate governance had no effect on tax avoidance. Likewise, corporate governance cannot moderate the effect of corporate social responsibility on tax avoidanceKeywords: corporate social responsibility disclosure, corporate governance, tax avoidance, GRI, Asean CG Scorecard, Cash ETR